Ketidaksetaraan Gender sebagai Bentuk Kekerasan Terhadap Perempuan di Jepang - Annisa Yuliana Sari; Shary Charlotte Henriette Pattipeilohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Japan is a developed nation with exellence economic growth and national stability. Unfortunately, in political, economic, education and family formation, Japan has a problem in a form of gender inequality. This research uses Feminism and its concept, Patriarchy and Hegemonic Masculinity, and Structural,Cultural and Direct Violence theory as a theoretical framework. Specifically, this research analyzes the forms of gender inequality against women using the said framework. The results of this study make clear that Japan’s gender inequality is a form of structural and direct violence, influenced by partriarchal culture of society that eventually shapes a social structure dominated by men, as seen in the imbalance of representation of women in politics, economic gap between men and women, access to education, along with social expecation to form a family towards women.